Characterization of Exotic Sorghum Germplasm Accessions for Protein, Carbohydrate Fractions and Energy Value under In Vitro Conditions - Singh, Sultan; Joshi, D. C.; Kumar, R. V.; Manjunatha, N. (Indian Journal of Animal Nutrition, 2017)
Twenty one sorghum exotic accessions with two checks CSV 15 and SSG 59-3 harvested at 50% flowering were evaluated for crude protein, carbohydrate fractions, protein fractions, digestibility, energy and in vitro methane production. Accessions differed (P<0.05) in crude protein, NDF, ADF, cellulose, lignin and EE contents. Structural and non structural carbohydrate contents varied (P<0.05) from 57.9 to 72.6 and 10.6 to 26.2% DM amongst the accessions. Mean contents of carbohydrate fraction B2 (slowly degradable) were highest (56.4) followed by rapidly degradable sugar (CA:24.61), lignin bound carbohydrate fraction (CC: 18.39) and intermediately degradable carbohydrate fraction (CB1: 0.56% TCHO), respectively. Mean soluble protein and non- protein nitrogen contents differed (P<0.05) among the accessions. The CP fractions PB1 (26.30), PB2 (20.77) and PB3 (21.50%) were higher (P<0.05) than PC (lignin bound protein fraction: 16.94% CP) and PA (15.36). In vitro DM digestibility and calculated values of DM intake and relative feed values differed (P<0.05) amongst the accessions. The value of TDN, DE and ME varied (P<0.05) among the accessions. The net energy efficiency for lactation (NEL), maintenance (NEM) and gain (NEG) were 1.21, 1.57 and 0.56 Kcal/g, respectively. In vitro methane production differed (P<0.05) amongst accessions. Accessions EC 512381, EC 512391, EC 512392, EC 512393 and EC 512394 were moderate to rich in CP, intake, DM digestibility and low in ADIN, structural carbohydrates and methane production than checks and other accessions. Accession EC 512392 was a distinct outliner and did not group with any other accession. Grouping of the accessions in different clusters and sub clusters indicated the existence of genetic diversity among the accessions for the various forage quality parameters.